Evaluation of a Three-Fluid Nozzle Spraying Process for Facilitating Spray Drying of Hydrophilic Polymers for the Creation of Amorphous Solid Dispersions - Lena Karin Mueller; Laura Halstenberg; Nicole Di Gallo; Thomas Kipping (MDPI AG, 2023)
Amorphous solid dispersions (ASDs) enable formulations to improve the solubility of poorly soluble active pharmaceutical ingredients (APIs). The amorphous state is reached through the disruption of the crystalline lattice of an API resulting in an increased apparent solubility with faster disintegration. Nevertheless, this form is characterized by a high-energy state which is prone to re-crystallization. To ensure a stable ASD, excipients, e.g., polymers that form a matrix in which an API is dispersed, are used. The applicable polymer range is usually linked to their solubility in the respective solvent, therefore limiting the use of hydrophilic polymers. In this work, we show the applicability of the hydrophilic polymer, polyvinyl alcohol (PVA), in spray-dried solid dispersions. Using a three-fluid nozzle approach, this polymer can be used to generate ASDs with a targeted dissolution profile that is characterized by a prominent spring and desired parachute effect showing both supersaturation and crystallization inhibition. For this purpose, the polymer was tested in formulations containing the weakly basic drug, ketoconazole, and the acidic drug, indomethacin, both classified as Biopharmaceutics Classification System (BSC) class II drugs, as well as the weakly basic drug ritonavir classified as BCS IV. Furthermore, ritonavir was used to show the enhanced drug-loading capacity of PVA derived from the advantageous viscosity profile that makes the polymer an interesting candidate for spray drying applications.